THE IMPACT OF CENTRAL CORNEAL THICKNESS ON VALUES OF INTRAOCULAR PRESSURE MEASURED WITH TWO METHODS: GOLDMANN APPLANATION AND DYNAMIC CONTOUR TONOMETRY IN PATIENTS WITH OPEN-ANGLE GLAUCOMA - Jordanova, Elena; Hantova-Senćanić, Paraskeva; Marjanovic, Ivan; Sencanic, Ivan; Stefanovic, Ivana; Baralic, Marko (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Objective. of this study was to evaluate the impact of corneal central thickness (CCT) on values of IOP measured with two methods: Goldmann applanation tonometry (GAT) and DCT.Methods. The study included 150 patients (300 yeas) with the open-angle glaucoma (54 males) mean age 59.39± 13.12 years. IOP was measured with two methods: GAT and DCT. CCT was measured (ultrasound pachymetry). DCT discovered one more value- ocular pulse amplitude (OPA).Results. IOP measured with GAT was lower compared to IOP measured with DCT (17.71±3.35mmHg vs 19.80± 3.67mmHg). Significantly positive association between IOP measured with GAT and IOP measured with DCT was found (r= 0.867, p< 0.01). In all patients significantly positive corelation between CCT and IOP measured with GAT (r=0.198, p< 0.01) and significantly positive corelation between CCT and IOP measured with DCT was found (r=0.180, p< 0.05). When changing CCT for every 10μm a change of IOP measured with GAT was for 0.3mmHg while the average change of IOP measured with DCT was for 0.4 mmHg. There was found significantly positive correlation between CCT and OPA (r=0.204, p< 0.01). Also, significantly positive association between OPA and IOP measured with GAT (r= 0.393, p< 0.01) as well as significantly positive association between OPA and IOP measured with DCT (r= 0.452, p< 0.01)  was found.Conclusion. IOP measured with GAT was lower than IOP measured with DCT. CCT has impact on both methods: GAT and DCT. The impact CCT on IOP (DCT) was lower compared to impact CCT on IOP(GAT).
Keywords: central corneal thickness, Dynamic contour tonometry, ocular pulse amplitude